Nilai-nilai Islam : perumusan ajaran dan upaya aktualisasi - Mughni, Syafiq A., 1954- (Yogyakarta : Pustaka Pelajar, 2001)
Islamic reform movement and Islam awakening in Indonesia.
Includes bibliographical references (p. 313-322).
Keywords: Islamic fundamentalism -- Indonesia; Islam and politics -- Indonesia; Islam and society -- Indonesia; Islam -- Indonesia